1978
DOI: 10.1007/bf00222423
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytological localization of LH, FSH, TSH and their subunits in the pituitary of normal and anencephalic human fetuses

Abstract: Immunostaining with antisera to oLH, hCG, hLH, pLHbeta, hFSH, hFSHbeta, hTSHalpha and bTSH was used to delineate the gonadotropic and thyrotropic cells of the human fetal anterior pituitary. Hypophyses from 29 normal fetuses, 3 newborn infants, and 5 totally ancencephalic fetuses were used. Several controls to check for the specificty of the immunocytological reaction were made. In normal fetuses, observations showed that: 1) the alpha subunit was detected from the eighth week and throughout gestation without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
2

Year Published

1981
1981
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 42 publications
2
34
2
Order By: Relevance
“…There is evi dence that pituitary production of free «-subunit decreases as production of TSH, FSH, and LH matures and the fetal hormone: «-subunit ratio approaches that of the adult [28]. Our findings confirm the maturation of «-subunit-contain ing cells as did the immunohistologic studies of other inves tigators [10,20,21]. It appears, therefore, that there is, dur ing fetal development, an «-subunit cell which may repre sent the precursor of the glycoprotein cell line and possibly the cell of origin of «-subunit-secreting adenomas [2], Thyrotrophin.…”
Section: Cell Differentiation In the Human Fetal Pituitarysupporting
confidence: 80%
“…There is evi dence that pituitary production of free «-subunit decreases as production of TSH, FSH, and LH matures and the fetal hormone: «-subunit ratio approaches that of the adult [28]. Our findings confirm the maturation of «-subunit-contain ing cells as did the immunohistologic studies of other inves tigators [10,20,21]. It appears, therefore, that there is, dur ing fetal development, an «-subunit cell which may repre sent the precursor of the glycoprotein cell line and possibly the cell of origin of «-subunit-secreting adenomas [2], Thyrotrophin.…”
Section: Cell Differentiation In the Human Fetal Pituitarysupporting
confidence: 80%
“…Immunohistochemical studies on the chronological cytogenesis of the adenohypophysis have been made in rats (SETALO andNAKANE, 1972, 1976;SETALO et al, 1976;TOUGARD et al, 1977;CHATELAIN et al, 1979;WATANABE and DAIKOKU, 1979), in mice (GROSS and BAKER, 1979) and in human fetuses (BAKER and JAFFE, 1975;BUGNON et al, 1977;DUBOIS et al, 1978). However, very little attention has been payed on the topographical distribution of the differentiating cells (BAKER and JAFFE, 1975;DUBOIS et al, 1978;GROSS and BAKER, 1979).…”
Section: Development Of the Pituitary Vascularizationmentioning
confidence: 99%
“…Immunohistochemical studies on the chronological cytogenesis of the adenohypophysis have been made in rats (SETALO andNAKANE, 1972, 1976;SETALO et al, 1976;TOUGARD et al, 1977;CHATELAIN et al, 1979;WATANABE and DAIKOKU, 1979), in mice (GROSS and BAKER, 1979) and in human fetuses (BAKER and JAFFE, 1975;BUGNON et al, 1977;DUBOIS et al, 1978). However, very little attention has been payed on the topographical distribution of the differentiating cells (BAKER and JAFFE, 1975;DUBOIS et al, 1978;GROSS and BAKER, 1979). In rats it has been shown that ACTH cells were first found in the ventro-medial portion of the pituitary on day 15.5 of gestation, TSH cells appeared in the posterior half of the pituitary on day 16.5, and LH cells were revealed one day later in a narrow ventral area in the anteromedial portion of the pituitary (WATANABE and DAIKOKU, 1979 Roles of the developing hypothalamus and the portal vessels.…”
Section: Development Of the Pituitary Vascularizationmentioning
confidence: 99%
“…Dubois, 1969 ;Dacheux and Dubois, 1976 ; pigs : Dacheux, 1978Dacheux, , 1981 ; sheep : Dubois and Mauleon, 1969 ; primates : Girod and Dubois, 1976 ;humans : Begeot et al, 1978 ;Dubois et al, 1978) and the hypothalamus Dubois and Barry ;1974 ;Paulin et al, 1977 ;Tramu et al, 1977 ;review in Barry, 1979 In figure 1 showing a 50-day fetus, the situation was somewhat different.…”
mentioning
confidence: 99%